Gifted education: A survey on the theories and models of giftedness - Tyrone O. Gil Jr. (Himpunan Pengembang Kurikulum Indonesia, 2025)
This paper explores the multifaceted landscape of gifted education, underpinned by diverse theoretical models that seek to define, identify, and nurture giftedness in individuals. The primary objective is to synthesize and critically examine these models, providing a comprehensive understanding of their historical context, key components, criticisms, and implications for educational practice. Through a systematic review of literature, the paper analyzes prominent theories and models, including those proposed by Lewis Terman, Francoys Gagné, Joseph Renzulli, Robert Sternberg, Howard Gardner, J.P. Guilford, George Betts, and Donald Treffinger and Edwin Selby. The findings reveal a rich array of perspectives on giftedness, moving from singular definitions to more nuanced understandings that encompass various domains, and highlight the importance of considering cognitive, creative, practical, and socio-emotional factors. The paper concludes by emphasizing the need for judicious application of these diverse theories and models to foster the potential of gifted learners and guide educators, policymakers, and parents in creating supportive learning environments. Abstrak Penelitian ini mengeksplorasi lanskap pendidikan berbakat yang multifaset, didasarkan pada berbagai model teoretis yang berusaha untuk mendefinisikan, mengidentifikasi, dan mengembangkan bakat pada individu. Tujuan utama penelitian ini adalah untuk mensintesis dan secara kritis mengkaji model-model ini, memberikan pemahaman komprehensif tentang konteks sejarah, komponen kunci, kritik, dan implikasinya untuk praktik pendidikan. Melalui tinjauan sistematis terhadap literatur, makalah ini menganalisis teori dan model terkemuka, termasuk yang diusulkan oleh Lewis Terman, Francoys Gagné, Joseph Renzulli, Robert Sternberg, Howard Gardner, J.P. Guilford, George Betts, serta Donald Treffinger dan Edwin Selby. Hasil temuan menunjukkan beragam perspektif tentang bakat, bergerak dari definisi tunggal ke pemahaman yang lebih halus yang mencakup berbagai domain, dan menyoroti pentingnya mempertimbangkan faktor kognitif, kreatif, praktis, dan sosial-emosional. Penelitian ini diakhiri dengan menekankan perlunya penerapan yang bijaksana dari berbagai teori dan model ini untuk memfasilitasi potensi pelajar berbakat dan membimbing pendidik, pembuat kebijakan, dan orang tua dalam menciptakan lingkungan belajar yang mendukung. Kata Kunci: bakat; pelajar berbakat; pendidikan berbakat; pengembangan bakat